2013
DOI: 10.1111/jsm.12248
|View full text |Cite
|
Sign up to set email alerts
|

Centrally Mediated Erectile Dysfunction in Rats with Type 1 Diabetes: Role of Angiotensin II and Superoxide

Abstract: Introduction Erectile dysfunction is a serious complication of diabetes mellitus. Apart from the peripheral actions, central mechanisms are also responsible for penile erection. Aim To determine the contribution of angiotensin (ANG) II in the dysfunction of central N-methyl-D-aspartic acid (NMDA)-nitric oxide (NO)-induced erectile responses in streptozotocin-induced type 1 diabetic (T1D) rats. Methods Three weeks after streptozotocin injections, rats were randomly treated with the angiotensin-converting en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Nonetheless, the possible proposed biochemical mechanism overwhelming mitochondrial oxidative stress of tempol is attributed to hydroxylamine reduction of tempol as well as nitroxide formation (Wang et al., ; Wilcox, ). Moreover, tempol has been reported to improve chronic high salt intake induced kidney injury (Carlström et al., ), and to be effective in preventing several of the adverse consequences of oxidative stress (Wilcox, ), and type 1 diabetes induced organ injury (Zheng et al., ) in animal models. Here, we demonstrated beneficial effects on alleviation of oxidative protein damage by tempol and stress tolerance in mimetic aging model of Drosophila .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the possible proposed biochemical mechanism overwhelming mitochondrial oxidative stress of tempol is attributed to hydroxylamine reduction of tempol as well as nitroxide formation (Wang et al., ; Wilcox, ). Moreover, tempol has been reported to improve chronic high salt intake induced kidney injury (Carlström et al., ), and to be effective in preventing several of the adverse consequences of oxidative stress (Wilcox, ), and type 1 diabetes induced organ injury (Zheng et al., ) in animal models. Here, we demonstrated beneficial effects on alleviation of oxidative protein damage by tempol and stress tolerance in mimetic aging model of Drosophila .…”
Section: Introductionmentioning
confidence: 99%
“…Exercise up-regulated nNOS expression within the PVN and improved the central component of the erectile dysfunction in diabetes mellitus ( Zheng et al, 2011 ). The level of neuronal NOS in the PVN was decreased in STZ-induced type 1 diabetic rats ( Zheng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…NMDA stimulates the same oxytocinergic pathways as dopamine, and there was ED and reduced expression of neuronal NOS in PVN . The authors found that both exercise and treatment with angiotensin II type 1 (AT 1 ) receptor antagonists improve erectile function in the streptozocin‐induced diabetic rat model , but the effect of dopaminergic drugs on erectile function remains to be investigated in animal models with diabetes.…”
Section: Modulation Of Dopaminergic Pathways and Unmet Needs In Patiementioning
confidence: 99%